T‐cell receptor diversity as a prognostic biomarker in melanoma patients. (3rd February 2020) - Charles, Julie; Mouret, Stephane; Challende, Isabelle; Leccia, Marie‐Therese; De Fraipont, Florence; Perez, Solene; Plantier, Nadia; Plumas, Joel; Manuel, Manuarii; Chaperot, Laurence; Aspord, Caroline
Abstract: There is increasing evidence that T‐cell receptor (TCR) repertoire diversity can be a predictive biomarker of immune responses in cancer patients. However, the characteristics of the T‐cell repertoire together with its prognostic significance in melanoma patients and impact on disease progression remain unknown. We investigated the combinatorial TCR repertoire diversity by semi‐quantitative multi‐N‐plex PCR in peripheral blood samples from 44 melanoma patients together with seven matched metastatic lymph nodes and explored its potential predictive value on clinical prognosis. The diversity was quantified by calculating both richness (number of different specificities) and evenness (relative abundance of the different specificities). Our results revealed that a higher TCR repertoire diversity in blood of patients was associated with a longer PFS, while divpenia (low repertoire diversity) was linked with poor prognosis. The diversity was significantly higher in patients undergoing late relapse and long survival compared to patients who progressed rapidly. Interestingly, the TCR repertoire diversity in tumor may have a potential prognostic value. Thus, our study highlights that the TCR repertoire diversity is a prognostic indicator of clinical outcome in patients with melanoma.